Method for modifying carbon felt electrode in zinc-bromine flow battery and zinc-bromine flow battery
By modifying the carbon felt electrode in zinc bromine flow battery, including pretreatment, precursor solution immersion and calcination, the problem of insufficient electrochemical activity and reversibility under high current density is solved, and the effect of significantly improving the battery performance and stability is achieved.
Patent Information
- Application Number
- CN202411838049.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-01
AI Technical Summary
The electrochemical activity and reversibility of carbon felt electrodes in existing zinc-brominate flow batteries at high current density are insufficient, and modification treatment is required to improve their performance.
The modified carbon felt electrode was obtained by pretreating the carbon felt electrode, preparing a precursor solution and soaking it therein, followed by calcining under a protective atmosphere, and cooling. The method includes tailoring and ultrasonic cleaning, using a precursor solution composed of nickel salts, nitrogen-containing heterocyclic compounds and carbon-based nanomaterials, and calcination treatment at different temperatures.
The electrochemical performance, power density, energy efficiency and cycle stability of zinc bromine flow batteries have been significantly improved, and the safety and reliability of their high-performance energy storage system components have been enhanced.
Smart Images

Figure CN119742379A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of electrochemical energy storage, and specifically relates to a method for modifying a carbon felt electrode in a zinc-bromine liquid flow battery and a zinc-bromine liquid flow battery. Background Art
[0002] Renewable energy sources such as wind and solar energy pose challenges to the quality of the power grid due to their volatility and discontinuity. Energy storage systems have become the key to solving this problem. Among them, zinc-bromine flow batteries have attracted attention because they can store surplus electricity in surplus periods and supply it in shortage periods. Zinc-bromine flow batteries are an important branch of flow batteries due to their high energy density, low cost, and environmental friendliness. However, the existing carbon felt electrodes used in zinc-bromine flow batteries have insufficient electrochemical activity and reversibility at high current densities, so they need to be modified to improve their performance. Summary of the invention
[0003] The main purpose of the present application is to provide a modification method for a carbon felt electrode of a zinc-bromine flow battery and a zinc-bromine flow battery. The present application can improve various properties including electrochemical properties of the carbon felt electrode by modifying the carbon felt electrode.
[0004] To achieve the above objectives, this application provides the following technical solutions:
[0005] A modification method for a carbon felt electrode in a zinc-bromine flow battery comprises: pretreating the carbon felt electrode; preparing a precursor solution; soaking the pretreated carbon felt electrode in the precursor solution; calcining the soaked carbon felt electrode under a protective atmosphere, and obtaining a modified carbon felt electrode after cooling to room temperature.
[0006] Optionally, the pretreatment of the carbon felt electrode includes: cutting the carbon felt electrode into a set size; immersing the carbon felt electrode cut into the set size in a mixed solution of acetone, water and ethanol, and cleaning it by ultrasonic cleaning, and after cleaning, drying it in a vacuum oven.
[0007] Optionally, the preparation of the precursor solution includes: dissolving the nickel salt and the nitrogen-containing heterocyclic compound in a polar solvent, and then continuing to add carbon-based nanomaterials to obtain a carbon-based nickel salt mixture; and using ultrasound to treat and disperse the carbon-based nickel salt mixture to obtain a precursor solution.
[0008] Optionally, the nickel salt includes any one of the following: nickel chloride hexahydrate, nickel nitrate hexahydrate and nickel sulfate hexahydrate.
[0009] Optionally, the polar solvent includes ethanol solution or N,N-dimethylformamide.
[0010] Optionally, the carbon-based nanomaterial includes any one of the following: reduced graphene oxide, graphene composite water-based conductive coating and carbon nanotubes.
[0011] Optionally, the pretreated carbon felt electrode is immersed in the precursor solution for 0.5 h to 2 h.
[0012] Optionally, the calcination temperature of the carbon felt electrode is 600° C. to 900° C., and the calcination time is 1 h to 3 h.
[0013] Optionally, the method further comprises: after the precursor solution is prepared, adding a surfactant and a template to the precursor solution.
[0014] In addition, the present application also provides a zinc-bromine liquid flow battery, which includes a modified carbon felt electrode, and the modified carbon felt electrode is prepared by the modification method of a carbon felt electrode in a zinc-bromine liquid flow battery as described in any of the preceding items.
[0015] This application can bring the following beneficial effects:
[0016] The present application not only significantly improves the electrochemical performance, power density, energy efficiency and cycle stability of the zinc-bromine flow battery by modifying the carbon felt electrode, but also enhances its safety and reliability as a component of a high-performance energy storage system. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic flow chart of a method for modifying a carbon felt electrode in a zinc-bromine flow battery provided by one embodiment of the present application;
[0018] Figure 2 It is a schematic diagram comparing the positive electrode cyclic voltammetry test results of the carbon felt electrode before and after modification provided in one embodiment of the present application;
[0019] Figure 3 It is a schematic diagram comparing the AC impedance test results of the carbon felt electrode before and after modification provided in one embodiment of the present application;
[0020] Figure 4 This is a schematic diagram comparing the energy efficiency of a carbon felt electrode before and after modification provided by an embodiment of the present application;
[0021] Figure 5 This is a schematic diagram comparing the long cycle performance of the carbon felt electrode before and after modification provided in one embodiment of the present application;
[0022] Figure 6 It is a schematic diagram of a comparison test of the bromine adsorption capacity of a carbon felt electrode before and after modification provided in one embodiment of the present application;
[0023] Figure 7It is a schematic diagram of UV-vis spectrum comparison of carbon felt electrodes before and after modification provided in one embodiment of the present application. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0025] It should be noted that all directional indications in the embodiments of the present application (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0026] In this application, unless otherwise clearly specified and limited, the terms "connection", "fixation", etc. should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0027] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present application, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by this application.
[0028] Figure 1 FIG. 1 is a schematic flow diagram of a method for modifying a carbon felt electrode in a zinc-bromine flow battery according to an embodiment of the present application, such as Figure 1 As shown, the modification method comprises the following steps:
[0029] S100: pre-treating the carbon felt (CF) electrode;
[0030] S200: preparing a precursor solution;
[0031] S300: soaking the pretreated carbon felt electrode in the precursor solution for 0.5 h to 2 h;
[0032] S400: placing the soaked carbon felt electrode in a tubular furnace at a temperature of 600° C., and calcining it for 1 to 3 hours under a protective atmosphere (for example, nitrogen gas), and after cooling to room temperature, obtaining a modified carbon felt electrode (graphene / NiO@CF).
[0033] In this step, for the carbon felt electrode, 600°C is the minimum effective calcination temperature. It has been verified by experiments that if the calcination temperature is less than 600°C, the precursors such as nickel nitrate hexahydrate and benzimidazole cannot be fully converted into uniformly distributed NiO nanoparticles, resulting in low purity of the formed NiO phase, affecting its electrochemical performance. In addition, if the temperature is too low (less than 600°C), the interfacial bonding force between the active material and the carbon felt substrate will be reduced. Once this bonding is not strong enough, it will affect the consistency and long-term stability of the carbon felt electrode, causing it to easily peel off or delaminate during the charge and discharge cycle.
[0034] It should be noted that the immersion time (0.5h to 2h) and calcination time (1h to 3h) of the pretreated carbon felt electrode in the precursor solution are proposed on the basis of comprehensive consideration of material properties and process requirements. Specifically, within the time range of 0.5h to 2h, the precursor solution can fully penetrate into the interior of the carbon felt electrode and form a preliminary covering layer on its surface. If the immersion time is less than 0.5h, the precursor will not be fully attached to the carbon felt electrode, resulting in uneven distribution of the subsequently generated active substances, thereby reducing the effective active area and electrochemical performance of the carbon felt electrode. On the contrary, if the immersion time is greater than 2h, the precursor will be excessively impregnated between the carbon felt fibers in the carbon felt electrode, resulting in excessive local concentration, which will in turn trigger the formation of precipitates or uncontrollable reactions, ultimately affecting the stability and consistency of the overall structure of the carbon felt electrode.
[0035] In addition, the calcination time of 1h to 3h is sufficient for the precursor to complete the necessary physical and chemical transformations such as decomposition and crystallization to form NiO nanoparticles with high crystallinity and good dispersibility. If the calcination time is too short (less than 1h), the precursor will not be fully converted into the target product, and the NiO nanoparticles will not be sufficiently crystallinity or unevenly distributed, thereby affecting the conductivity and electrochemical activity of the carbon felt electrode. On the contrary, if the calcination time is too long (greater than 3h), although the crystallinity of the precursor can be improved to a certain extent, it also increases the risk of excessive sintering of the NiO nanoparticles, that is, the NiO nanoparticles may grow and form larger agglomerates, reducing the active surface area and consuming more energy. In addition, too long a time may also cause thermal damage to the carbon felt electrode itself, destroying its original pore structure and mechanical strength.
[0036] In summary, selecting 0.5 to 2 h as the soaking time range and 1 to 3 h as the calcination time range is the best result that comprehensively considers the process feasibility while ensuring the optimal performance of NiO nanoparticles, carbon felt substrate and the composite structure formed between them.
[0037] Based on the above embodiment, in step S100, the pretreatment of the carbon felt electrode includes the following steps:
[0038] S101: Cut the carbon felt electrode into a set size, for example, the size after cutting is 3×3 cm 2 ;
[0039] S102: The carbon felt electrode cut into a set size is immersed in a mixed solution of acetone, water and ethanol, and is ultrasonically cleaned for 30 minutes. After cleaning, it is dried in a vacuum oven at 60°C.
[0040] Based on the above embodiment, in step S200, the preparation of the precursor solution includes the following steps:
[0041] S201: 1.449 g (5 mmol) of nickel nitrate hexahydrate and 1.18 g (10 mmol) of benzimidazole are dissolved in 50 ml of ethanol solvent, and then 3 g of graphene composite water-based conductive coating is added to obtain a carbon-based nickel salt mixture;
[0042] S202: using ultrasound to treat and disperse the carbon-based nickel salt mixture for 30 minutes to obtain a precursor solution.
[0043] In another exemplary embodiment, the present application also provides an electrode modification method for a zinc-bromine flow battery. Different from the above-mentioned embodiment, the present method places the soaked carbon felt electrode in a tubular furnace at a temperature of 900° C. for calcination.
[0044] In this embodiment, for the carbon felt electrode, 900°C is the highest effective calcination temperature. It has been verified by experiments that when the calcination temperature exceeds 900°C, it will cause excessive sintering of NiO nanoparticles and other active substances, causing the NiO nanoparticles to grow and form larger agglomerates, thereby reducing the active surface area, reducing the number of effective sites for electrochemical reactions, and ultimately weakening the electrochemical performance of the carbon felt electrode. In addition, if the temperature is too high, it may cause changes in the internal pore structure of the carbon felt, and even cause it to partially melt or decompose, thereby seriously affecting the mechanical strength and electronic conduction path of the carbon felt electrode, and thus affecting the overall performance of the battery.
[0045] In another exemplary embodiment, the present application also provides an electrode modification method for a zinc-bromine flow battery. Different from the above-mentioned embodiment, the present method places the soaked carbon felt electrode in a tubular furnace at a temperature of 800° C. for calcination.
[0046] In this embodiment, it has been experimentally verified that 800°C is the optimal calcination temperature for the carbon felt electrode. The reason is that calcining the carbon felt electrode at 800°C can cause the NiO nanoparticles to form a more regular and uniformly distributed structure. Such a structure helps to improve the crystallinity of the NiO nanoparticles, thereby enhancing their structural stability, thereby improving the conductivity and electrochemical activity of the carbon felt electrode. In addition, at this temperature, the surface of the carbon felt electrode can be modified, so that the carbon felt electrode has better conductivity, higher electrochemical activity and stronger bromine adsorption capacity. These factors work together to significantly improve the overall performance of the zinc-bromine flow battery, including energy efficiency, power density and cycle stability. Further, compared with lower (600°C) or higher (900°C) calcination temperatures, 800°C can effectively activate the desired chemical reaction while minimizing the occurrence of unwanted side reactions. For example, too low a temperature may lead to incomplete decomposition of the precursor, while too high a temperature may cause excessive sintering or other adverse changes in the carbon felt electrode, thereby affecting the electrochemical properties of the carbon felt electrode.
[0047] In another exemplary embodiment, the present application also provides an electrode modification method for a zinc-bromine flow battery. Different from the aforementioned embodiment, in the present method, nickel chloride hexahydrate is used to replace nickel nitrate hexahydrate during the preparation of the precursor solution.
[0048] In this embodiment, nickel chloride hexahydrate has a higher solubility in water than nickel nitrate hexahydrate, which helps to ensure that nickel ions (Ni 2+ ) are evenly dispersed in the solution to form a uniform precursor solution; in addition, the chloride ions in the nickel chloride can accelerate the kinetic process of the chemical reaction and promote faster precipitation or complexation reactions, thereby shortening the preparation time of the precursor solution.
[0049] In another exemplary embodiment, the present application also provides an electrode modification method for a zinc-bromine flow battery. Different from the aforementioned embodiment, in the present method, nickel sulfate hexahydrate is used to replace nickel nitrate hexahydrate or nickel chloride hexahydrate during the preparation of the precursor solution.
[0050] In this embodiment, compared with nickel nitrate and nickel chloride, nickel sulfate has lower toxicity and is less harmful to the environment and operators. In addition, the use of nickel sulfate can avoid the introduction of nitrate ions or chloride ions, thereby reducing possible harmful byproducts or corrosion problems, especially in a battery environment, where chloride ions may cause corrosion of metal parts, and nitrate ions may decompose at high temperatures to produce harmful gases. Further, experimental studies have shown that when nickel sulfate is used as a precursor, it can guide the formation of a more regular and evenly distributed NiO nanostructure, thereby improving the crystallinity and electrochemical activity of NiO nanoparticles, so that the formed NiO nanoparticles have better conductivity and higher structural stability, which in turn helps to improve the electrochemical performance of the carbon felt electrode.
[0051] In another exemplary embodiment, the present application also provides an electrode modification method for a zinc-bromine flow battery. Different from the above-mentioned embodiment, in the process of preparing the precursor solution, the present method uses a polyamine compound (such as ethylenediamine or triethylenetetramine) to replace benzimidazole.
[0052] In this embodiment, the polyamine compound contains multiple amino functional groups and can form a multi-dentate coordination structure with nickel ions. This strong coordination effect can not only stabilize the nickel ions in the precursor solution, but also help maintain the morphology and size stability of NiO nanoparticles during the calcination process. In addition, the polyamine compound can change the electronic structure of the carbon felt electrode surface, exposing more active sites, thereby promoting the occurrence of electrocatalytic reactions. At the same time, since the polyamine compound can provide more active sites and its own conductivity is better than that of benzimidazole, it can effectively reduce the electrochemical polarization, thereby further improving the energy efficiency and power density of the battery.
[0053] In another exemplary embodiment, the present application also provides an electrode modification method for a zinc-bromine flow battery. Different from the above-mentioned embodiment, in the present method, an imidazole derivative (such as 1-methylimidazole or 2-methylimidazole) is used to replace benzimidazole during the preparation of the precursor solution.
[0054] In this embodiment, the imidazole derivatives have strong coordination ability and can form stable complexes with metal ions. Compared with benzimidazole, imidazole derivatives such as 1-methylimidazole or 2-methylimidazole can coordinate with metal ions more effectively through their nitrogen atoms. This strong coordination can help guide NiO nanoparticles to form a more uniform and regular distribution during the pyrolysis process, thereby improving the crystallinity of NiO nanoparticles. In addition, compared with benzimidazole, imidazole derivatives have better solubility, which helps to ensure the uniform dispersion of all components in the precursor solution and reduce agglomeration. At the same time, the good solubility and dispersibility of imidazole derivatives mean that NiO nanoparticles can be deposited more evenly on the surface of the carbon felt electrode, increasing the number of effective active sites, thereby improving the overall electrochemical performance of the carbon felt electrode.
[0055] In another exemplary embodiment, the present application also provides an electrode modification method for a zinc-bromine flow battery. Different from the above-mentioned embodiment, in the present method, N,N-dimethylformamide (DMF) is used to replace the ethanol solvent during the preparation of the precursor solution.
[0056] In this embodiment, N,N-dimethylformamide (DMF) is a highly polar aprotic polar solvent with a high dielectric constant and good solubility. Compared with ethanol, N,N-dimethylformamide (DMF) can more effectively prevent the agglomeration of nanoparticles, thereby ensuring the uniform distribution of active substances on the entire electrode. In addition, due to the high boiling point of N,N-dimethylformamide (DMF) (about 153°C), it can remain in liquid state at relatively high temperatures, thereby providing a more stable reaction environment.
[0057] In another exemplary embodiment, the present application also provides an electrode modification method for a zinc-bromine flow battery. Different from the aforementioned embodiment, in the present method, reduced graphene oxide (rGO) is used to replace the graphene composite water-based conductive coating during the preparation of the precursor solution.
[0058] In this embodiment, reduced graphene oxide (rGO) retains most of the conductive properties of graphene, but compared with graphene composite water-based conductive coating, reduced graphene oxide (rGO) is more easily dispersed in water, and its surface contains a certain amount of functional groups, which helps to improve its interaction with other materials. In addition, compared with pure graphene, the sheet structure of reduced graphene oxide (rGO) has, first, a large number of edge positions and other defective parts are exposed, which often become ideal places for catalytic reactions and can promote electrochemical reactions on the electrode surface, such as bromine adsorption and redox reactions in zinc-bromine flow batteries; second, the sheet structure can be embedded between other active materials, playing the role of skeleton support, which can enhance the mechanical strength of the carbon felt electrode and prevent the carbon felt electrode from structural damage or peeling caused by volume changes during the charge and discharge cycle.
[0059] In another exemplary embodiment, the present application also provides an electrode modification method for a zinc-bromine flow battery. Different from the aforementioned embodiment, in the present method, carbon nanotubes (CNTs) are used to replace the graphene composite water-based conductive coating during the preparation of the precursor solution.
[0060] In this embodiment, carbon nanotubes (CNTs) have extremely high conductivity and can provide an efficient electron transfer path for the carbon felt electrode. Compared with graphene composite water-based conductive coatings, carbon nanotubes (CNTs) can more effectively reduce the resistance of the carbon felt electrode, thereby improving the overall energy efficiency of the battery. In addition, carbon nanotubes (CNTs) can form a three-dimensional conductive network on the surface of the carbon felt electrode. This conductive network structure can not only enhance the connection between the electrode materials, but also promote the rapid transfer of electrons from the active material to the current collector, thereby improving the power density of the battery. More importantly, compared with graphene, carbon nanotubes (CNTs) have better durability and fatigue resistance, which means that carbon nanotubes (CNTs) can maintain stable electrochemical properties in long-term charge and discharge cycles, thereby effectively extending the service life of the carbon felt electrode and even the entire battery.
[0061] It is worth noting that carbon nanotubes (CNTs) have a unique tubular structure that can expose more active sites, which are ideal sites for catalytic reactions and are conducive to electrochemical reactions on the surface of carbon felt electrodes, such as bromine adsorption and redox reactions in zinc-bromine flow batteries. In contrast, the sheet structure of reduced graphene oxide (rGO) may partially cover the active sites, thereby limiting the effective electrochemical reaction to a certain extent. Therefore, this application selects carbon nanotubes (CNTs) as the best carbon-based nanomaterial for preparing the precursor solution.
[0062] In another exemplary embodiment, the present application also provides an electrode modification method for a zinc-bromine flow battery. Different from the aforementioned embodiment, after preparing the precursor solution, the present method further adds a surfactant and a template to the precursor solution, wherein the surfactant includes: an ionic surfactant (cationic: for example, hexadecyltrimethylammonium bromide (CTAB), dodecylpyridinium chloride; anionic: for example, sodium dodecyl sulfate (SDS), sodium dodecylbenzene sulfonate (SDBS); zwitterionic: for example, cocamidopropyl betaine (CAB)) or a non-ionic surfactant (polyoxyethylene ethers: for example, Tween series (Tween), Span series (Span); polyol esters: for example, sucrose fatty acid esters, sorbitan fatty acid esters). The template includes any of the following: a hard template (inorganic material: such as silica (SiO2), alumina (Al2O3) nanoparticles or porous membranes; metal organic frameworks: such as ZIF-8 or UiO-66), a soft template (polymer micelles: such as polyethylene oxide-polypropylene oxide (PEO-PPO) diblock copolymers; biological molecules: such as DNA, proteins).
[0063] In this embodiment, by adding surfactants and templates to the precursor solution, the performance of the carbon felt electrode can be significantly improved. Specifically, the surfactant can effectively prevent the aggregation of metal oxide (such as NiO) nanoparticles and ensure their uniform distribution on the surface of the carbon felt. This uniform coverage helps to increase the active area of the entire carbon felt electrode, thereby improving its electrochemical performance. In addition, the surfactant can also improve the coating effect of graphene or other conductive materials on the carbon felt, forming a more continuous and smooth coating, which not only increases the conductivity of the electrode, but also reduces the interface resistance, which is beneficial to the conduction of current. Furthermore, for a hydrophobic substrate such as carbon felt, the surfactant can also increase its hydrophilicity, making it easier for the electrolyte to penetrate into the interior of the carbon felt electrode, improving the ion transfer path, and thereby improving the overall efficiency of the battery.
[0064] In addition, the use of templates can construct metal oxide nanomaterials with specific morphologies (such as porous structures, fibrous or lamellar structures) on carbon felt. These special structures provide a larger specific surface area and better mass transfer characteristics, which is beneficial to improving the electrochemical activity of carbon felt electrodes. Furthermore, the special structures formed by the templates often have higher thermal and chemical stability, which helps to maintain the performance of carbon felt electrodes in long-term cyclic use, thereby extending the service life of the battery.
[0065] In summary, by adding surfactants and templates to the precursor solution, the physicochemical properties of the carbon felt electrode can be significantly improved, and its electrochemical performance as a zinc-bromine flow battery electrode can be improved, including but not limited to higher energy efficiency, lower impedance, better cycle stability and stronger bromine adsorption capacity.
[0066] The present application realizes the modification of the carbon felt electrode based on the above embodiments. Compared with the carbon felt electrode before modification, the modified carbon felt electrode has the following characteristics:
[0067] 1. After modification, NiO nanoparticles are evenly distributed on the surface of carbon felt and form a composite structure with graphene. This uniform distribution increases the number of effective active sites and improves the overall active area of the carbon felt electrode. In addition, the presence of graphene constructs an efficient electron transmission path, enhances the connection between electrode materials, and promotes the rapid transfer of electrons from active materials to current collectors, thereby improving the power density of the battery. Furthermore, graphene and NiO nanoparticles not only provide additional structural support, but also improve the mechanical strength of the carbon felt electrode, which can reduce its structural damage or peeling caused by volume changes during the charge and discharge cycle.
[0068] 2. NiO nanoparticles as catalysts can significantly improve the electrochemical activity of carbon felt electrodes, especially the catalytic efficiency in redox reactions, such as the adsorption and release of bromine. This means that the modified carbon felt electrodes can participate in electrochemical reactions more effectively and improve energy conversion efficiency. In addition, due to the good conductivity and more active sites provided by graphene, the modified carbon felt electrodes can effectively reduce electrochemical polarization and reduce overvoltage losses, thereby improving the energy efficiency of the battery.
[0069] Next, the present application further performs performance tests on the carbon felt electrodes before and after modification, and makes comparative descriptions, wherein the tests specifically include electrochemical tests, charge and discharge performance tests, bromine adsorption capacity tests, and long cycle stability tests.
[0070] 1. Electrochemical test:
[0071] The carbon felt electrodes before and after modification were subjected to positive electrode cyclic voltammetry (CV) test and electrochemical impedance spectroscopy (EIS) test. Figure 2 and Figure 3 As shown in the figure, after testing, the reduction peak current value of the modified carbon felt electrode is 90mA / cm 2 Compared with the carbon felt electrode before modification (54mA / cm 2 ) increased by 70%, indicating that the improved carbon felt electrode has higher electrochemical reaction activity, which means higher power density and faster charge and discharge rate for the battery. The impedance of the modified carbon felt electrode is 0.2Ω·cm 2Compared with the carbon felt electrode before modification (0.5Ω·cm 2 ) decreased by 60.1%, indicating that the contact resistance between the carbon felt electrode and the electrolyte was significantly reduced. The lower impedance helps to reduce energy loss, allowing the battery to operate at a lower voltage drop, thereby improving the overall energy efficiency. The redox peak potential difference (ΔE) of the modified carbon felt electrode is 39mV, which is 13.3% lower than that of the carbon felt electrode before modification (45mV), indicating that the reversibility of the electrochemical reaction of the modified carbon felt electrode has been enhanced. The smaller ΔE means that the redox reaction between the positive and negative electrodes is more balanced, reducing the occurrence of irreversible reactions, thereby extending the service life of the battery.
[0072] 2. Charge and discharge performance test:
[0073] At different current densities (20, 40, 80, 120, 160 mA / cm 2 ) were tested for charge and discharge of the carbon felt electrodes before and after modification to evaluate their energy efficiency. Figure 4 and Figure 5 As shown, at 20mA / cm 2 At the current density, the energy efficiency of the modified carbon felt electrode is 88%, which is 22% higher than that of the unmodified carbon felt electrode (72%). In addition, at higher current densities (40, 80, 120, 160 mA / cm 2 ), the energy efficiency of the modified carbon felt electrode increased by 13%, 31%, 48% and 74% respectively.
[0074] In summary, as the current density increases, the energy efficiency of the modified carbon felt electrode not only does not drop sharply, but maintains a high level. This feature enables the battery to withstand a higher discharge rate without sacrificing too much energy conversion efficiency, which is very important for application scenarios that require fast charging and discharging, such as electric vehicles and peak frequency regulation in smart grids.
[0075] 3. Bromine adsorption capacity test:
[0076] Visual adsorption experiments were performed on the carbon felt electrodes before and after modification, such as Figure 6 As shown, the carbon felt electrodes before and after modification were immersed in Br2 solution (a solution formed by bromine dissolved in a specific solvent, which is yellow) and left to stand for 5 minutes. By comparison, it can be found that the Br2 solution of the unmodified carbon felt electrode is still yellow, while the Br2 solution of the modified carbon felt electrode is almost colorless, indicating that the adsorption capacity of the modified carbon felt electrode for bromine is much stronger than that of the unmodified carbon felt electrode. Further, as Figure 7As shown, the present application conducted UV-vis spectral analysis on the carbon felt electrode before and after modification, wherein, in the spectrum of the carbon felt electrode before modification, the characteristic peak at a wavelength of 270 nm still exists (the presence of an obvious characteristic peak at 270 nm means that the unmodified carbon felt electrode fails to effectively adsorb the bromine or polybromine ions in the solution, so the bromine or polybromine ions still exist in the solution and maintain their original absorption characteristics, and the bromine or polybromine ions have specific electronic transitions, and they tend to absorb light near a wavelength of 270 nm. Therefore, when the solution contains bromine or polybromine ions, an obvious absorption peak will appear around 270 nm); while in the spectrum of the modified carbon felt electrode, the characteristic peak at a wavelength of 270 nm almost disappears (the almost disappearance of the characteristic peak indicates that the modified carbon felt electrode has significantly adsorbed bromine or polybromine ions, so that the amount of bromine or polybromine ions in the solution is greatly reduced), therefore, it can be confirmed that graphene / NiO@CF has an excellent absorption capacity for bromine and polybromine ions. In zinc-bromine flow batteries, the reactions occurring on the positive electrode side involve the reduction (during charging) and oxidation (during discharging) of bromine. If the carbon felt electrode can better adsorb bromine or polybromine ions, it can provide more active sites to promote these reactions. This means that at the same current density, charge transfer can be more efficient, thereby improving the energy conversion efficiency of the battery.
[0077] 4. Long cycle stability test:
[0078] The carbon felt electrodes before and after the improvement were subjected to 300-cycle long-cycle tests. After 300 cycles, the energy efficiency of the carbon felt electrode before the modification decreased from 77% to 50%, with a retention rate of only 65%, a coulombic efficiency of 75%, and a voltage efficiency of 67%; while the energy efficiency (EE%) of the modified carbon felt electrode decreased from 82% to 80%, with an energy efficiency retention rate of 98%, a coulombic efficiency (CE%) of 92%, and a voltage efficiency (VE%) of 87%. The modified electrode can maintain a high energy efficiency, and the energy efficiency retention rate is as high as 98%, which means that the zinc-bromine flow battery can maintain a high-efficiency working state for a longer time, thereby reducing the need for frequent replacement or maintenance. In addition, the high levels of coulombic efficiency and voltage efficiency also indicate the high reversibility and low loss of the internal reactions of the battery, which helps to extend the overall service life of the battery.
[0079] Based on the above tests, it is not difficult to find that the various properties of the modified carbon felt electrode prepared by the method described in the present application are greatly improved compared with the carbon felt electrode before modification.
[0080] In another exemplary embodiment, the present application also provides a zinc-bromine liquid flow battery, wherein the zinc-bromine liquid flow battery comprises a modified carbon felt electrode, and the modified carbon felt electrode is prepared as described in any of the previous embodiments.
[0081] In this embodiment, the zinc-bromine flow battery using modified carbon felt electrodes (such as graphene / NiO@CF) exhibited significantly improved electrochemical performance, cycle stability and bromine adsorption capacity, achieving higher energy efficiency and lower electrochemical polarization. This electrode greatly improves the energy conversion efficiency of the battery at different current densities by constructing an efficient electron transfer path and providing more active sites, and maintains excellent performance stability in long cycle tests. In addition, its optimized physicochemical properties and environmental friendliness further enhance the safety and reliability of the battery, making it an ideal choice for high-performance energy storage systems.
[0082] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A method for modifying a carbon felt electrode in a zinc-bromine flow battery, characterized in that: The modification method comprises: Pre-treating the carbon felt electrode; preparing a precursor solution; soaking the pretreated carbon felt electrode in the precursor solution; The soaked carbon felt electrode is calcined under a protective atmosphere and cooled to room temperature to obtain a modified carbon felt electrode.
2. The method according to claim 1, characterized in that: The pretreatment of the carbon felt electrode comprises: Cutting the carbon felt electrode into a set size; The carbon felt electrode cut into a set size is immersed in a mixed solution consisting of acetone, water and ethanol, and is cleaned by ultrasonic cleaning. After cleaning, it is dried in a vacuum oven.
3. The method according to claim 1, characterized in that The preparation of the precursor solution comprises: Dissolving a nickel salt and a nitrogen-containing heterocyclic compound in a polar solvent, and then adding a carbon-based nanomaterial to obtain a carbon-based nickel salt mixture; The carbon-based nickel salt mixture is treated and dispersed by using ultrasonic waves to obtain a precursor solution.
4. The method according to claim 3, characterized in that The nickel salt includes any one of the following: nickel chloride hexahydrate, nickel nitrate hexahydrate and nickel sulfate hexahydrate.
5. The method according to claim 3, characterized in that: The polar solvent includes ethanol solution or N,N-dimethylformamide.
6. The method according to claim 3, characterized in that The carbon-based nanomaterial includes any one of the following: reduced graphene oxide, graphene composite water-based conductive coating and carbon nanotube.
7. The method according to claim 1, characterized in that The pretreated carbon felt electrode is immersed in the precursor solution for 0.5 h to 2 h.
8. The method according to claim 1, characterized in that The calcination temperature of the carbon felt electrode is 600° C. to 900° C., and the calcination time is 1 h to 3 h.
9. The method according to claim 1, characterized in that: The method further comprises: After the precursor solution is prepared, a surfactant and a template are added to the precursor solution.
10. A zinc-bromine flow battery, characterized in that: The zinc-bromine liquid flow battery comprises a modified carbon felt electrode, and the modified carbon felt electrode is prepared by the modification method of a carbon felt electrode in a zinc-bromine liquid flow battery according to any one of claims 1 to 9.
Citation Information
Patent Citations
Nickel-nickel oxide heterostructure catalyst, electrode and preparation method and application of nickel-nickel oxide heterostructure catalyst and electrode
CN116895770A
Cited By
Biomass derived carbon skeleton modified graphite felt electrode and preparation method and application thereof
CN122202346A
Zinc-bromine flow battery and preparation method thereof
CN122494728A
A zinc-bromine flow battery and a method of making the same
CN122494728B